Integrating Density Functional Theory Modeling with Experimental Data to Understand and Predict Sorption Reactions: Exchange of Salicylate for Phosphate on Goethite - Kubicki, James D.; Ohno, Tsutomu (Soil systems, 2020)
Density functional theory (DFT) calculations are a quantum mechanical approach that can be used to model chemical reactions on an atomistic scale. DFT provides predictions on structures, thermodynamics, spectroscopic parameters and kinetics that can be compared against experimentally determined data. This paper is a primer on the basics of utilizing DFT for applications in mineral-water interfaces. In our case-study, we use DFT to model the surface complexes of phosphate and salicylate adsorbed onto the (101) and (210) surfaces of α-FeOOH (goethite), as an example of combining DFT and experiment. These three components are important in the phosphorus-organic matter interactions in soils, and by comparing the energies of the two surface complexes, the exchange energy of salicylate for phosphate onto goethite can be estimated. The structures of the surface complexes are predicted and the resulting vibrational frequencies calculated based on these structures are compared to previous observations. Upon verification of reasonable surface complex models, the potential energy of exchanging salicylate for phosphate is calculated and shown to be significantly exothermic. This model result is consistent with observations of plant exudates, such as salicylate freeing adsorbed phosphate in soils under P-limited conditions.